PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP PRESTASI KERJA GURU SEKOLAH DASAR PADA UNIT PELAKSANA TEKNIS DINAS DAERAH (UPTD) PENDIDIKAN, PEMUDA DAN OLAHRAGA KECAMATAN JEUNIEB KABUPATEN BIREUEN - Majid, Abdul; Bariah, Chairul (indOmera, 2021)
The purpose of this study was to determine 1) the influence of the principal's leadership on teacher performance, 2) the influence of organizational culture on teacher performance, 3) the influence of the work environment on teacher performance, and 4) the influence of the principal's leadership, organizational culture and work environment on performance. Elementary school teacher at the Regional Office for the Technical Implementation Unit for Education, Youth and Sports, Jeunieb District, Bireuen Regency. Methods of data analysis with a path analysis approach. The results showed that: a). There is an influence of the principal's leadership on teacher performance by 12.74%. b). There is an influence of organizational culture on teacher performance by 10.95%, and c). There is an influence of the work environment on teacher work performance by 21.95%. Based on the magnitude of the determination coefficient of 0.509, it is explained that the contribution of the aspects of the principal's leadership, organizational culture and work environment to teacher performance is 50.9%